Measuring and Testing Complementarity and Co-evolution in Financial Systems - Adeline Saillard; Thomas Url (Austrian Institute of Economic Research (WIFO), 2013)
The distinction between bank- and market-based economies has a long tradition in applied macroeconomics. The two types of financial architecture differ not only with respect to the amount of funds channelled through private banking versus the capital market but with respect to several other characteristics, suggesting a competitive rather than a complementary relation between bank- and market-based institutions. Following the idea of Song and Thakor (2010) we test for the hypothesis that the efficiency of financial systems increases for more balanced financial systems, featuring both kinds of institutions in equal measure. We compute an index of complementarity and relate this index and other variables representing various feedback channels of co-evolution to measures for the efficiency of credit and capital markets in a panel of industrial countries.
Keywords: 330; Internationaler Finanzmarkt; Finanzsystem; Welt